ANALYSIS OF FACTORS INFLUENCING THE VALUE OF 3 STAR HOTELS IN MEDAN CITY - David Koko E. C. O. Naibaho; Sukaria Sinulingga; Nazaruddin, Nazaruddin (Journal of Innovation Research and Knowledge, 2022)
The purpose of this research is to find out analysis of factors influencing the value of 3 Star Hotels in Medan City. The research that has been put forward, this research is classified as causality research. The population used in this study is 3 Star Hotels in Medan City which has been assessed by the Public Appraisal Service Office. The sample in this study, the number of samples is 30 for 3 Star Hotels in Medan City. The analysis used in this research is multiple linear regression analysis. The results of the study show that room rate, occupancy rate, and number of room have a significant effect on the value of 3 Star Hotels in Medan City. Operational cost have no a significant effect on the value of 3 Star Hotels in Medan City.